2010
DOI: 10.4103/1319-3767.58765
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome after Swenson′s operation for Hirshsprung′s disease

Abstract: Background/Aim:Hirschsprung's disease (HD) is one of the most common causes resulting in lower intestinal obstruction in children with atypical clinical symptoms and inconspicuous morphological findings by barium enema X-ray. Recently, this situation has been largely ameliorated by improvement of instrument for measurement of anorectal pressure. By now, anorectal manometry has been regarded as a routine means for functional assessment and diagnosis of HD. It is accurate in nearly all cases of HD with character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 16 publications
1
25
1
Order By: Relevance
“…In the literature, several authors stated that patients with true incontinence present a significantly lower resting pressure than normal subjects. 24,27 As also reported by Gad ElHak et al, 25 in a study of 52 patients after pull-through operation, the mean pressure was 58.1 ± 15.1 mmHg among continent cases, 49.1 ± 15.1 mmHg among minor incontinent cases, and 37.1 ± 12.1 mmHg among major incontinent cases with a highly significant difference between continent and major incontinent groups. On the other hand, Meinds et al 10 reported a wide range of anal resting pressure 70 (25-110) mmHg.…”
Section: Anal Resting Pressuresupporting
confidence: 75%
See 3 more Smart Citations
“…In the literature, several authors stated that patients with true incontinence present a significantly lower resting pressure than normal subjects. 24,27 As also reported by Gad ElHak et al, 25 in a study of 52 patients after pull-through operation, the mean pressure was 58.1 ± 15.1 mmHg among continent cases, 49.1 ± 15.1 mmHg among minor incontinent cases, and 37.1 ± 12.1 mmHg among major incontinent cases with a highly significant difference between continent and major incontinent groups. On the other hand, Meinds et al 10 reported a wide range of anal resting pressure 70 (25-110) mmHg.…”
Section: Anal Resting Pressuresupporting
confidence: 75%
“…30 So, it raised an hypothesis that the normally innervated bowel anastomosed to the anal canal acquires a "quite normal" rectal function as an adaptation of the neo-rectum years after a pull-through operation. 25 However, re-establishment of RAIR was not clinically correlated with any positive long-term outcome in our series as well as in the other studies. 9 Of course, a RAIR re-establishment due to technical issues should be always considered.…”
Section: Rectal Anal Inhibitory Reflexcontrasting
confidence: 67%
See 2 more Smart Citations
“…The incidence may vary from 1% to as high as 37.7%. [19][20] In this study only 3 patients complained of soiling The mean operation time from incision to dressing was 115.16±16.17minutes the mean hospital stay was 7.15 ± 1.85days. (Table-IV Postoperative complications were evaluated immediately and on 2nd, 4th, 8th and 12th weeks following operations to seeshort term outcome of children who have undergone the Classic swensonabdominoperineal pull through operation in the treatment of Hirschsprung's disease.Five patients needed perioperative blood transfusion.…”
Section: Discussionmentioning
confidence: 67%